Mechanical, but not infective, pacemaker erosion may be successfully managed by re-implantation of pacemakers. Issue 2 (February 1994) - Griffith, M. J.; Mounsey, J. P.; Bexton, R. S.; Holden, M. P.
Abstract : OBJECTIVE--When a pacemaker box causes erosion it is usually removed and a new pacemaker implanted at a contralateral site. In this study when there was no evidence of systemic infection an attempt was made to clean and reimplant the same pacemaker in the same site. RESULTS--Over 10 years 62 patients had pacemaker reimplantation. In 18 patients the procedure was repeated a second time. Reimplantation was successful after at least six months follow up in 38 patients (61%): in nine two attempts had been made. Mean hospital stay for all patients was 21.3 days; for patients in whom the procedure was successful it was 12.5 days and for those in whom it was unsuccessful it was 35.4 days. 31 (82%) of the 38 patients in whom reimplantation was successful had no bacterial growth from wound swabs from 17/24 (71%) patients in whom reimplantation was unsuccessful (p < 0.001). Bacteria were grown from swabs from 7/8 patients with a protruding wire compared with 9/23 patients with a protruding pacemaker (p = 0.05). Thin patients and those who were older were more likely to have successful reimplantation: neither association reached statistical significance. A clinical impression of infection was not helpful. If re-implantation had been attempted only in the patients with negative wound swabs or intact skin the success rate would have been 74% at a cost of 5010 pounds per patient compared with a cost of 6509 pounds per patient for explantation and a reimplantation of a new contralateral pacemaker. CONCLUSION--These data support the hypothesis that pacemaker erosion is caused by primary infection or by a non-infective process (probably mechanical pressure). Pacemaker erosion that is not caused by infection can be successfully managed by ipsilateral reimplantation and this approach saves money.